Analisis Kualitas Audit Akibat Kebijakan PPKM saat Pandemi Covid-19 - Rifai, Zainur (ISAS, 2022)
Implementation of audit practices on financial reports by auditors, aims to assess compliance and adherence of entities to regulations, that is financial accounting standards in their preparation. The policy of Community Activities Restrictions Enforcement (CARE) due to the covid-19, limiting the implementation of audits so that they cannot run normally and are carried out by remote auditing. This limitation resulted in the public doubting the quality of the audit on the reliability of the financial statements. With this issue in mind, research was conducted to find out how audit quality was when CARE was implemented during the pandemic. This research was carried out using the method of literature study or literature review, by examining or critically reviewing knowledge, ideas, or findings obtained from within an academically oriented body of literature and formulating theoretical and methodological contributions for certain topics. From the research that has been done, the existence of CARE (Community Activities Restrictions Enforcement) reduces the quality of audits of financial reports. Keywords: audit quality, remote audit, covid-19.